(untitled) (Research, Society and Development, 2023)
Facial aging is a natural process that results in the loss of collagen, leading to wrinkles, sagging and visible fine lines. External factors, such as sun exposure and unhealthy habits, can accelerate this process. Collagen loss is a common aesthetic concern, driving the search for treatments to stimulate its production and minimize the effects of time on the skin. Several options are available in dermatology and aesthetics, such as the application of hyaluronic acid for filling and hydration, in addition to the use of lasers and radiofrequency to stimulate collagen production. Adopting a skin care routine and a balanced diet are also recommended to delay aging. Hyaluronic acid injection techniques in orofacial harmonization have gained popularity as a non-surgical alternative to improve facial aesthetics, offering versatile and personalized results. However, it is crucial that such procedures are performed by experienced and qualified professionals, ensuring safety, patient satisfaction and respect for the individuality of each one. Therefore, this narrative review aims to analyze and synthesize the available literature on facial aging and collagen loss, as well as hyaluronic acid injection techniques in orofacial harmonization.